Analysis of Tourism Area Development in Bukit Lawang, North Sumatra - Khairul Azmi; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the development of the Bukit Lawang tourism area. The research employs descriptive and qualitative data analysis, focusing on a problem-solving approach that is based on descriptions rather than numerical data. The purpose of using a qualitative research method is to facilitate a better understanding of information from the sources used as data, providing an effective comprehension of the ecotourism development strategy being studied. The qualitative analysis involves data collection through interviews, observations, documentation, and other methods. The research findings indicate that income from the development of the Bukit Lawang tourism sector has not significantly impacted the local revenue (PAD) of Langkat Regency as a whole. This is because Bukit Lawang tourism has not been fully implemented and managed effectively by the government. Tourism and conservation activities in Bukit Lawang have yet to be supported by proper tourism area planning, which is essential for sustainable tourism. The land division by the government is currently limited to conservation areas, plantations, and community-owned lands. Sustainable tourism land use planning would make Bukit Lawang a more responsive area. Achieving a sustainable tourism area in Bukit Lawang requires the involvement of both the government and local communities.